Personal income distribution and progressive taxation in a neo-Kaleckian model: Insights from the Italian case - Maria Cristina Barbieri Góes (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2019)
This paper develops a stylized short-run neo-Kaleckian model incorporating personal income inequality and income taxes based on You and Dutt (1996). The main goal is to investigate how changes in income taxes and personal income distribution affect output growth. The theoretical discussion of the stylized model is then empirically assessed, using data for Italy retrieved from the Survey of Household Income and Wealth published by the Bank of Italy. The empirical analysis confirms both the heterogeneity of the propensities to consume of Italian households and the dominance of absolute income effects in the Italian consumer behavior that assures the negative trade-off between inequality and aggregate demand. More specifically, it is shown that, overall, Italians are still income constrained, not allowing for a compensation of the demand-depressing effects of raising inequality via debt and wealth-based consumption. Likewise, it is argued that decreasing personal income inequality via progressive income tax reforms would have positive effects on aggregate demand, utilization, and growth.
Keywords: D11; D12; D31; E12; E21; H24; 330; Income inequality; Personal Income Distribution; Income Taxes; Kaleckian model